Blood-volume In the Hemoglobinless Antarctic Teleost Chionodraco-hamatus (Lonnberg) - R. ACIERNO; J. A. MACDONALD; B. TOTA; AGNISOLA, CLAUDIO (Journal of Experimental Zoology, 1995)
Blood volume in the hemoglobinless Antarctic icefish Chionodraco hamatus (Channichthyidae) has been determined by the Evans blue dye dilution technique. A mean blood volume of 127.0 +/- 5.0 mi kg(-1) body weight was found, a value even higher than that previously found in another icefish, Chaenocephalus aceratus (mean blood volume, 89.7 mi kg(-1) body weight; Hemmingsen and Douglas [1970] Comp. Biochem. Physiol., 33:733-744; Twelves [1972] Br. Antarct. Surv. Bull. 31:85-92). This extraordinary hypervolemia appears unique among teleosts and may compensate for the absence of hemoglobin in the icefish. (C) 1995 Wiley-Liss, Inc.